An assessment of fire safety measures in healthcare facilities in Nigeria. Issue 3 (14th December 2020) - Ebekozien, Andrew; Aigbavboa, Clinton; Ayo-Odifiri, Solomon Oisasoje; Salim, Nuzaihan Aras Agus
Abstract : Purpose: The occurrence of fire accidents in hospital buildings has become a serious challenge and more serious in developing nations. The purpose of this paper intends to assess fire safety measures in Nigerian hospital facilities. The significance of this study is to ensure that the design and construction of hospital facilities enhance the safety of users and properties. Design/methodology/approach: The data were collected via a case study and questionnaire survey and administered to the facility users. The study survey is to assess the respondents' perception of fire safety measures in hospital facilities and suggest possible policy measures that will be employed to enhance safety. Findings: This paper found that 91% of the respondents have awareness of fire safety measures in hospital facilities. Electrical faults and combustible materials were identified as the frequent causes of fire occurrences in hospital facilities. This can be averted where flammable materials and electrical appliances are correctly installed, and safety rules enforced. Findings show that safety rules are lax in public than standard private hospitals. Research limitations/implications: This paper is limited to fire safety measures in Nigerian healthcare facilities. Future research is needed to evaluate the level of compliance from design, construction and post-construction of precautionary fire safety measures in hospital facilities in Nigeria. Practical implications: This paper recommended that designers and hospital administrators should improve on fire safety measures via the development of fire safety management plan and education. Thus, enforcement of fire safety measures in hospital facilities as specified in building codes should be implemented and monitored during and after the design of the hospital buildings. Findings provide valuable lessons on how to improve the fire safety measures in healthcare facilities across the states and other developing countries with similar healthcare situations. Originality/value: This paper demonstrates that the stakeholders, especially government agencies concern with approval and enforcement of fire safety measures in healthcare facilities need to reawaken to her responsibility because of the lax implementation across the states.